Primary renal leiomyosarcoma: a rare entity - Beigh, Ambreen; Sheikh, Junaid; Sheikh, Bilal; Mujo, Shaheena Parveen; Summyia, Farooq (International Journal of Research in Medical Sciences, 2018)
Background: Primary leiomyosarcoma of the kidney is an exceptionally rare tumor with an aggressive behavior. However, reported literature is very limited. Since the prognosis for a renal sarcoma is extremely poor, differentiation from sarcomatoid renal cell carcinoma (RCC) is necessary. Histopathology and immunohistochemistry are the only modes of diagnosing these sarcomas as they have no specific diagnostic features clinically and radiologically. Objectives was to evaluate the clinicopathological pattern of leiomyosarcomas arising from kidney. Methods: This study was conducted in the Department of Pathology, Government Medical College, Srinagar. It was a retrospective study done over a period of 3 years, July 2014 to June 2017. A total of 4 patients, who underwent surgery and were diagnosed with primary LMS of the kidney, were included in the present study. Results: The study was done to evaluate the clinicopathological pattern of 4 cases of primary renal LMS diagnosed at a tertiary care hospital. Age of the patients ranged from 35-64 years with a mean age of 53.5 years. Sex ratio of 1:1 was observed. Major presenting symptom was flank pain (75%) followed by mass abdomen (50%). Also, one of the patients presented with spontaneous rupture of kidney. Radical nephrectomy was done in all patients. On gross examination tumor had originated from renal pelvis (50%) in 2 patients, renal vein (25%) in one patient whereas, renal capsule (25%) appeared to be the site of origin in other patient. Histopathological examination and immunohistochemistry proved the lesion as primary leiomyosarcoma of kidney. Conclusions: Being a rare tumour, renal leiomyosarcoma needs to be considered in the differential diagnosis of renal masses even in patients younger than 40 years.